PCR detection of Candidatus Liberibacter asiaticus, the agent of Huanglongbin or greening disease in citrus - D.K. GHOSH; Y.S. AHLAWAT, V.K. BARANWAL*, S. MAZUMDER, JITENDER SINGH, V. SURYANARAYANA (Indian Phytopathology, 2004)
The causal agent of Huanglongbing (HLB) or citrus greening disease (CGD) was detected from total DNA isolated from midrib of leaves of citrus trees from Delhi, Jammu and Maharashtra showing symptoms of yellowing or yellow mottling by PCR amplification of ribosomal protein gene. The amplicon was cloned in pGEM-T easy vector and sequenced. The clone was 703 nucleotide long and showed 100 % nucleotide sequence identity with part of b operon gene of Asian species of greening bacterium i.e. Candidatus Liberibacter asiaticus but differed from African species of greening bacterium i.e. Candidatus Liberibacter africanus. Our studies indicated that b operon gene of Asian species of greening bacterium is highly conserved and can be used for quick detection of greening bacterium in citrus plant for phytosanitary and certification programme.